ANALISIS KESEMPATAN KERJA DI PROVINSI SULAWESI UTARA - Muchlis ., Suratinoyo; Oktavianus ., Porajouw; Martha M. Sendow (AGRI-SOSIOEKONOMI, 2017)
This study aims to describe the development of employment and analyze changes in the structure of employment by employment and employment status in North Sulawesi Province. This study uses secondary data of Population Census, National Labor Force Survey, and North Sulawesi in Figures 2010 and 2015. Data analysis using simple calculation method, that is data according to employment and job status calculated percentage then displayed in table and graph form to explain about changes of labor structure in North Sulawesi Province. The results showed that employment opportunities according to employment in North Sulawesi Province dominated by three sectors, namely the agricultural sector, service sector, and trade sector. Sectors in the secondary sector are low in providing employment opportunities in North Sulawesi. If employment is simplified into three sectors, namely primary, secondary and tertiary sectors, then the largest employment opportunities are in the tertiary sector (trade, transportation, finance, services), then primary (agriculture), and the lowest in the secondary sector (mining , industry, electricity and buildings). Based on employment status, the highest percentage is to work as a worker/employee/employee with an increasing tendency. However, when grouped into formal and informal sectors, the highest employment opportunity is in the informal sector. Based on the result of the research, it is concluded that job opportunity of agriculture sector still dominates employment in North Sulawesi. The role of agriculture/primary sector in providing job opportunities decreased; on the contrary the service sector/tertiary role was increasing. Employment opportunities by employment status in North Sulawesi, the highest percentage is employed as laborers/employees/employees. The role of the formal sector in providing employment increases, while the informal sector is declining.